KERAGAMAN PAKAN TARSIUS (Tarsius wallacei Merker., et al, 2010) di LEBANU, MARAWOLA, SIGI, SULAWESI TENGAH - Nobertus Bumbugan; Annawaty Annawaty; Yulius Duma (Biology Department, Mathematics and natural science, Tadulako University, 2017)
Tarsius wallacei is an endemic mammal of Sulawesi published by Merker, et al on 2010. Even though the distributions, vocalizations and morphometric have been studied well, the ecological aspect especially type of feed was not studied whereas the diet information is an important data for conservation of this endemic species. The objective of the study was collect the variety of tarsius’s prey in the wild. A collection of samples has been conducted from February to October 2015 using sweep net, light trap, and hand capture methods. The results of prey collection show that Tarsius wallacei feed on insects. Thirteenspecies were found as a prey of Tarsius wallacei which consists of 10 order, i.e. Orthoptera, Blattodea, Coleoptera, Araneae, Lepidoptera, Hemiptera, Odonata, Isoptera, Hymenoptera and Homoptera. Proximate analysis of the three orders that belong to the group Insecta indicated the Tarsius wallacei probably consume mainly on Orthoptera with the highest protein content, 69.32%, followed by Lepidoptera (66.51%), and Coleoptera (41,98%)